2022
DOI: 10.2147/rru.s359872
|View full text |Cite
|
Sign up to set email alerts
|

A Drug-Coated Balloon Treatment for Urethral Stricture Disease: Three-Year Results from the ROBUST I Study

Abstract: Introduction Endoscopic management of male anterior urethral stricture disease is common; however, repeat treatment is associated with high recurrence rates. Here, we report the 3-year results of the ROBUST I trial, which evaluated the safety and efficacy of the Optilume ® drug coated balloon (DCB) in men with recurrent urethral strictures. Methods Adult men with recurrent bulbar urethral strictures ≤2 cm in length and 1–4 prior endoscopic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Balloons coated with drugs such as paclitaxel have achieved promising clinical results in recent years. Two studies on paclitaxel-coated balloons for recurrent urethral strictures revealed the considerable effect of these devices on recurrent urethral strictures, with a relatively objective functional success rate (67%) and an anatomical success rate (74.6%) 27 28. The functional success rate was defined as the percentage of subjects with ≥50% improvement in IPSS scores who did not require retreatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Balloons coated with drugs such as paclitaxel have achieved promising clinical results in recent years. Two studies on paclitaxel-coated balloons for recurrent urethral strictures revealed the considerable effect of these devices on recurrent urethral strictures, with a relatively objective functional success rate (67%) and an anatomical success rate (74.6%) 27 28. The functional success rate was defined as the percentage of subjects with ≥50% improvement in IPSS scores who did not require retreatment.…”
Section: Resultsmentioning
confidence: 99%
“…Patients’ subjective perception of improvement in voiding symptoms is a crucial indicator of the true efficacy of urethral stricture treatment, and the results are summarised in table 4 . The ROBUST III study 28 revealed that patients’ International Prostate Symptom Score-Quality of Life scores increased significantly by 30 days after balloon dilation, indicating outstanding short-term efficacy. Moreover, 3-year follow-up results from the ROBUST I trial study 27 indicated significant improvements in both QoL scores and Patient-Reported Outcome Measure for Urethral Stricture Surgery scores for patients who underwent balloon dilation compared with baseline status (p<0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The 3-year outcomes for the same drug-coated balloon from the Robust I trial demonstrated a 67% functional success. 20 Although drug-coated balloons are approved by the FDA for anterior urethral strictures, the trial was not powered to assess results patients with penile urethra strictures; therefore, the Panel recommends that drug-coated balloons are restricted to treat patients with recurrent bulbar urethral strictures. Furthermore, the efficacy of repeated use of the drug-coated balloon has not been ascertained and is not recommended.12.…”
Section: Guideline Statementsmentioning
confidence: 99%
“…9 Treatment with paclitaxel-coated balloons has also been shown to significantly reduce the rate of stricture recurrence in men with urethral strictures. 10,11 This study compares the safety and efficacy of Optilume BPH to a sham surgical procedure for the treatment of LUTS secondary to BPH with outcomes reported through 12 months of follow-up.…”
mentioning
confidence: 99%